2022
DOI: 10.1007/s10140-021-02013-1
|View full text |Cite
|
Sign up to set email alerts
|

Vascular findings in CTA body and extremity of critically ill COVID-19 patients: commonly encountered vascular complications with review of literature

Abstract: The purpose of our review is to discuss the role of CT angiography (CTA) in evaluating a variety of vascular complications in critically ill COVID-19 patients. The COVID-19 pandemic continues to be a worldwide health threat. While COVID-19 pneumonia is the most common and well-recognized presentation of COVID-19, severely ill hospitalized patients often present with extrapulmonary systemic findings. Vascular complications occur not only due to known viral-induced vasculopathy, coagulopathy, and related “cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…The most common hemorrhagic complication is hematomas involving the retroperitoneum, abdominal wall, gluteal regions, or upper thigh. Both blockage of major arteries and solid organ infarction, such as the intestinal tract, kidneys, pancreas, and liver, are examples of thrombotic events seen on CT angiography [11]. The CT findings of the abdomen and pelvis of our patient exhibited right retroperitoneal hematoma and right renal artery non-occlusive filling defect that might be due to the anticoagulation therapy.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The most common hemorrhagic complication is hematomas involving the retroperitoneum, abdominal wall, gluteal regions, or upper thigh. Both blockage of major arteries and solid organ infarction, such as the intestinal tract, kidneys, pancreas, and liver, are examples of thrombotic events seen on CT angiography [11]. The CT findings of the abdomen and pelvis of our patient exhibited right retroperitoneal hematoma and right renal artery non-occlusive filling defect that might be due to the anticoagulation therapy.…”
Section: Discussionmentioning
confidence: 59%
“…Lee stated that in comparison to non-vascular observations, vascular findings are rather uncommon. Both thrombotic and hemorrhagic adverse events occur in COVID-19 patients, with hemorrhagic events being more common [11]. The most common hemorrhagic complication is hematomas involving the retroperitoneum, abdominal wall, gluteal regions, or upper thigh.…”
Section: Discussionmentioning
confidence: 99%
“…This study disagreed with the previous research by Vadvala et al [ 20 ] which reported that the bleeding complications with or without contrast extravasation were most commonly seen in 71% of included patients, while thromboembolic and ischemic complications were seen only in 17.8% of patients. Other worldwide researchers also disagreed with this, including Shah et al [ 21 ], Lodigiani et al [ 22 ], Lee et al [ 23 ], O'Shea et al [ 24 ], Abdelmohsen et al [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the abdomen and pelvis, hemorrhagic complications were more common than thrombotic complications, including hematomas of retroperitoneum and abdominal wall. 73 Overall, rates of VTE among patients hospitalized with COVID-19 are approximately three-fold higher than among historical matched controls 74 , whereas rates of arterial thromboembolism are lower. 75 …”
Section: Introductionmentioning
confidence: 93%
“…The frequent occurrence of VTE when not clinically suspected is corroborated on postmortem studies. 72 While rare, aortic thrombosis, occlusion of large vessels, and solid organ infarct have been reported 73 . In the abdomen and pelvis, hemorrhagic complications were more common than thrombotic complications, including hematomas of retroperitoneum and abdominal wall.…”
Section: Introductionmentioning
confidence: 99%